Pension funds and urban investment: four models of financial intermediation. - Clark, G (Pion Ltd., 1997)
It has been often suggested that public and private pension funds should be, and could be, mobilised to invest in urban infrastructure, housing, and community development. In fact, given the apparent decline in government funding of such areas of concern, it has been suggested that pension funds may be the only 'new' sources of finance in the near future. In this paper, I assess the current state of play in the pension fund investment management industry, noting the conservatism of many fund trustees with respect to alternative investment products (AIPs) as well as noting that standard models of asset allocation hardly ever allocate significant resources to such products. It is argued that the rate of adoption and the level of funding of AIPs depend upon solutions to two basic interrelated problems associated with AIPs: the high costs of imperfect information and the lack of adequate measures of product providers' veracity. A set of four institutional solutions to these problems are reviewed, with a focus put upon the design and implementation of AIPs in relation to conventional financial markets. This leads to a consideration of the proper role of government policy with respect to AIPs and the long-term potential of AIPs with respect to product innovation in financial markets in general.